1998
DOI: 10.1093/hmg/7.4.671
|View full text |Cite
|
Sign up to set email alerts
|

Localization of motor-related proteins and associated complexes to active, but not inactive, centromeres

Abstract: Multicentric chromosomes are often found in tumor cells and certain cell lines. How they are generated is not fully understood, though their stability suggests that they are non-functional during chromosome segregation. Growing evidence has implicated microtubule motor proteins in attachment of chromosomes to the mitotic spindle and in chromosome movement. To better understand the molecular basis for the inactivity of centromeres associated with secondary constrictions, we have tested these structures by immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…Despite this, only one of the two identical sites forms an active neocentromere. This situation parallels that found in pseudo-dicentric or pseudo-multicentric chromosomes arising from translocation events where only one centromere remains active [Faulkner et al, 1998;Page et al, 1995;Sullivan et al, 1995]. Presumably, the same mechanism that prevents more than one centromere on these chromosomes from becoming active operates in the inv dup(20) case to prevent both arms of the inverted duplication from forming neocentromeres.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Despite this, only one of the two identical sites forms an active neocentromere. This situation parallels that found in pseudo-dicentric or pseudo-multicentric chromosomes arising from translocation events where only one centromere remains active [Faulkner et al, 1998;Page et al, 1995;Sullivan et al, 1995]. Presumably, the same mechanism that prevents more than one centromere on these chromosomes from becoming active operates in the inv dup(20) case to prevent both arms of the inverted duplication from forming neocentromeres.…”
Section: Discussionsupporting
confidence: 69%
“…The chromosome is present in 100% of cells examined from blood lymphocytes and transformed lymphoblast and fibroblast cell cultures, indicating faithful chromosome segregation. Immunofluorescence using antibodies against centromere proteins CENP-A, CENP-C, CENP-E, CENP-F, and INCENP, all considered as markers for active centromeres [Chan et al, 1998;Faulkner et al, 1998;Kalitsis et al, 1998;Mackay et al, 1998;Sullivan et al, 1994;Sullivan and Schwartz, 1995;Thrower et al, 1995], provided further evidence for the presence of a functional centromere on the constricted arm of the inv dup(20p) chromosome. Two lines of evidence suggest the formation of this functional centromere through the activation of a neocentromere on the inv dup(20p) chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…13). An alternative possibility is that after integration, one centromere sequence is silenced, which is one mechanism observed to prevent instability in dicentric chromosomes (60,61). However, our observation of only one centromere-like DNA sequence per chromosome based on ChIP-seq experiments would suggest that this is not the case, at least in recent diatom evolutionary history.…”
Section: Discussionmentioning
confidence: 77%
“…Direct proof of centromere function in the low-alphoid chromosomes has come from immunocytochemical studies using antibodies against two functionally important centromere proteins, CENP-C and CENP-E. CENP-C has been reported to regulate kinetochore structural integrity (Tomkiel et al 1994) and to be essential for mitosis as evident from a lethal phenotype in gene knockout studies (Fukagawa and Brown 1997;Kalitsis et al 1998), whereas CENP-E is a molecular motor that has been shown to move chromosomes along microtubules (Thrower et al 1995). The importance of CENP-C and CENP-E in centromere function is further suggested by the observation that these proteins are found on active, but not inactive, centromeres in dicentric or multicentric chromosomes (Earnshaw et al 1989;Page et al 1995;Sullivan and Schwartz 1995;Faulkner et al 1998). Thus, the detection of both of these antigens on each of the lowalphoid centromere cases has provided direct support for the functional integrity of these centromeres.…”
Section: Wwwgenomeorgmentioning
confidence: 99%